MEASUREMENT OF THE E+E- -] B(B)OVER-BAR AND E+E- -] C(C)OVER-BAR FORWARD BACKWARD ASYMMETRIES AT THE Z0 RESONANCE - Adriani, O; Aguilarbenitez, M; Ahlen, S; Akbari, H; Alcaraz, J; Aloisio, A; Alverson, G; Alviggi, M; Ambrosi, G; An, Q; Anderhub, H; Anderson, A; et al. (1992)
We have measured the forward-backward asymmetry in e+e-→bb and e+e-→cc processes using hadronic events containing muons or electrons. The data sample corresponds to 4100000 hadronic decays of the Z0. From a fit to the single lepton and dilepton p and pT spectra, we determine Abb=0.086±0.015±0.007 and Acc=0.083±0.038±0.027 at the effective center-of-mass energy √s=91.24 GeV. These measurements yield a value of the electroweak mixing angle sin2 θw=0.2336±0.0029. © 1992.